2007
DOI: 10.1099/mic.0.2007/008391-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel bacterial disease of the European shore crab, Carcinus maenas – molecular pathology and epidemiology

Abstract: A novel bacterial disease of the European shore crab, Carcinus maenas -molecular pathology and epidemiology Several rickettsia-like diseases have been reported in arthropods (insects and crustaceans), some of which result in significant losses of economically important species such as shrimp and crabs. This study reports on the molecular pathology of a recently emerged disease of the European shore crab, Carcinus maenas, termed milky disease -named as a result of the unusual milky appearance of the haemolymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…6d). Environmental stress and infection have been shown to cause elevation of glucose levels (Eddy et al 2007;Hall and van Ham 1998). Lorenzon et al (1997) reported an increase in hemolymph glucose in several crustacean taxa following injection of lipopolysaccharide (LPS).…”
Section: Challenge Samplesmentioning
confidence: 99%
“…6d). Environmental stress and infection have been shown to cause elevation of glucose levels (Eddy et al 2007;Hall and van Ham 1998). Lorenzon et al (1997) reported an increase in hemolymph glucose in several crustacean taxa following injection of lipopolysaccharide (LPS).…”
Section: Challenge Samplesmentioning
confidence: 99%
“…Assays were performed as described in detail previously (Eddy et al 2007, Powell & Rowley 2007. Histopathology.…”
Section: Methodsmentioning
confidence: 99%
“…5 ml of Bouin's seawater fixative through unsclerotised membranes. Tissues were processed, stained and examined as described previously (Eddy et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…(Tubiash et al, 1975;Wang, 2011). Intracellular bacterial infections occur within specific types of host cell (see Vincent et al, 2004;Eddy et al, 2007). Fungal pathogens (Phycomycetes, Ascomycetes and Fungi Imperfecti) have been implicated in catastrophic epidemics and mortality events in decapod crustaceans (Unestam, 1973).…”
Section: Diseases Of Crustaceansmentioning
confidence: 99%